Digitalization and sustainability in the automotive industry : the role of connected services : a qualitative case study at the example of the German original equipment manufacturer BMW - Fey, Florian (2023)
Considering the fundamental changes in the automobile industry, connected services are playing an increasingly essential role for OEMs, as they enable new business models and income streams plus offer the prospect of differentiation from the competition. Furthermore, they are critical for meeting the industry's everchanging customer expectations and can make a significant contribution to ecologically sustainable transportation. As a result, it is critical to understand the present state of connected services. The aim of the research of this master thesis is therefore to evaluate to what extent connected services can positively influence ecologically sustainable mobility in the automotive industry. For this purpose, the following research questions are posed: How can connected services contribute to more sustainable mobility? And which services can have the most significant impact? A qualitative empirical study concentrating on the German OEM BMW was conducted to answer those research questions. Specifically, the study investigates existing literature about connected services, analyses their current environmental impact and proposes a future forecast. The evaluation of these results shows that connected services positively influence sustainability by contributing to emission reduced/energyefficient mobility (due to improved driving behavior and efficient navigation) and by transparently visualizing the ecological footprint of individual mobility. In addition, the holistic ecological impact will grow in the future, since on the one hand connected services will be developed that will be focused on improved sustainability, and on the other hand, the overall usage of connected services will grow in the future, which increases their ecological impact.